Designing for print an in-depth guide to planning, creating, and producing successful design projects - Conover, Charles (Wiley, 2011)
"This book is a single-source guide to planning, designing and printing successful projects using the Adobe Creative Suite 5. Packed with real-world design exercises, this revised edition is fully updated to align with CS5. Now in full color throughout, along with dozens of sidebars and step-by-step descriptions, this complete resource walks readers through the design process in the same order actual projects are implemented, with content that progresses from planning through execution. Graphic designers are sure to increase their skill and boost their creativity with the use of this book"-- Provided by publisher.